Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.131.105.1993
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and Dispersal Patterns of Sediments in the Turbidite Wedge of Nankai Trough

Abstract: Drill core recovered at Ocean Drilling Program Site 808 (Leg 131) proves that the wedge of trench sediment within the central region of the Nankai Trough comprises approximately 600 m of hemipelagic mud, sandy turbidites, and silty turbidites. The stratigraphic succession thickens and coarsens upward, with hemipelagic muds and volcanic-ash layers of the Shikoku Basin overlain by silty and sandy trench-wedge deposits. Past investigations of clay mineralogy and sand petrography within this region have led to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 80 publications
1
41
0
Order By: Relevance
“…Coring of the upper intervals at Site C0012 was likewise deferred until Expedition 333. Previous studies in the Nankai-Shikoku region showed that hemipelagic mud(stones) change in composition largely as function of depositional age (e.g., Chamley, 1980;Chamley et al, 1986;Underwood et al, 1993aUnderwood et al, , 1993bSteurer and Underwood, 2003;Guo and Underwood, 2012;Underwood and Guo, 2013). Hemipelagic sedimentation during the Miocene was dominated by expandable clay minerals (smectite group), whereas the proportions of detrital illite and chlorite increased steadily through the Pliocene and Quaternary.…”
Section: Introductionmentioning
confidence: 99%
“…Coring of the upper intervals at Site C0012 was likewise deferred until Expedition 333. Previous studies in the Nankai-Shikoku region showed that hemipelagic mud(stones) change in composition largely as function of depositional age (e.g., Chamley, 1980;Chamley et al, 1986;Underwood et al, 1993aUnderwood et al, , 1993bSteurer and Underwood, 2003;Guo and Underwood, 2012;Underwood and Guo, 2013). Hemipelagic sedimentation during the Miocene was dominated by expandable clay minerals (smectite group), whereas the proportions of detrital illite and chlorite increased steadily through the Pliocene and Quaternary.…”
Section: Introductionmentioning
confidence: 99%
“…Kastner et al, 1993). The observed freshening is partly explained by in situ diagenesis (compaction and thermally driven smectite dehydration) but also suggests some episodic lateral fluid flow along one or more sediment horizons (Moore, Taira, Klaus, et al, 2001;Saffer and Bekins, 1998;Underwood et al, 1993).…”
Section: Heat and Fluid Flowmentioning
confidence: 89%
“…Kastner et al, 1993). The observed freshening is partly explained by in situ diagenesis (i.e., compaction and thermally driven smectite dehydration) but also suggests some episodic lateral fluid flow along one or more sediment horizons (Moore, Taira, Klaus, et al, 2001;Saffer and Bekins, 1998;Underwood et al, 1993).…”
Section: Heat and Fluid Flowmentioning
confidence: 93%